Association of Chemical stress with Type I & II diabetes - Noushad , Shamoon; Akhtar, Hamza; Ali, Safdar; Abbasi, Zafar Iqbal; Ahmed , Sadaf; Mehdi, Soobhi; Kaneez Fatima; Saleem, Saima (International Journal of Endorsing Health Science Research, 2015)
Background Diabetes mellitus is characterized by absolute or relative deficiencies in insulin secretion or insulin action correlated with chronic hyperglycemia and other disturbances in carbohydrate, lipid and protein metabolism results in weakening immunity. In addition, various biochemical disorders associated with diabetic vascular complications, such as hyperlipidemia and oxidative stress frequently co-exist with diabetes mellitus. Previous studies have also suggested that these and additional factors might involve with increasing chemical stress in diabetic patients. Material and methods The questionnaire based survey was conducted including both close & open ended questions along with the assessment of chemical stress using Sadaf Stress Scale (SSS) version 2 among diabetic patients. This study was conducted in tertiary care hospitals of Karachi from October 1st till November 10th, 2014. Data was analyzed and plotted using SPSS version 20.0. Results This study showed that 28% of diabetic patients were in severe chemical stress. However, the various symptoms of severity included body temperature alterations (50%), feeling of dehydration (56%) and shortness of breath (63%) were obtained. Conclusion It is concluded that the diabetes patient with type 2 diabetes are at higher risk of developing chemical stress that may indicate multiple metabolic and as indicated by prominent symptoms that can be a oxidative alterations on sequence of increase use of medications and altered glucose metabolism.